Differences in the Rates of Drug Polyconsumption and Psychiatric Comorbidity among Patients with Cocaine Use Disorders According to the Mental Health Service. Issue 4 (8th August 2017) - Araos, P.; Vergara-Moragues, Esperanza; González-Saiz, Francisco; Pedraz, María; García-Marchena, Nuria; Romero-Sanchiz, Pablo; Ruiz, Juan Jesus; Campos-Cloute, Rafael; Serrano, Antonia; Pavón, Francisco Javier; Torrens, Marta; Rodriguez De Fonseca, Fernando
ABSTRACT: Cocaine continues to be a worldwide public health concern in Europe. To improve prognosis and intervention, it is necessary to understand the characteristics of the patients who depend on the services where they receive care. The objective is to analyze the differences among patients who use cocaine and between ambulatory and residential resources to better adapt treatment. This is a descriptive, observational study of two populations of cocaine users in treatment: the ambulatory therapeutic community (ATC) and the therapeutic community (TC). The PRISM diagnostic interview was used for both groups. An analysis of both populations indicates a high prevalence of cocaine, heroin, cannabis, sedative, psychostimulant, and hallucinogen use disorders in the TC population compared to the ATC. In alcohol use disorder, differences between both mental health services were not observed. The degree of severity of cocaine use disorders (CUD) is greater in the TC population. The prevalence of psychiatric comorbidity is not statistically significant between the two populations, except for primary psychotic disorders, which are more prevalent in the TC population. This difference in the prevalence of psychotic disorders may be related to the high prevalence of cannabis use disorders in TC patients. Differences in the prevalence of substance use disorders, severity of CUD, and psychiatric comorbidity may limit the efficiency of mental health services involved in substance use disorder therapeutics. These results suggest the need for careful and extensive phenotyping of patients to improve intervention and prognosis in a clinical resource-dependent manner.